Indinavir, Nevirapine, Stavudine, and Lamivudine for Human Immunodeficiency Virus–Infected, Amprenavir-Experienced Subjects: AIDS Clinical Trials Group Protocol 373 - Gulick, Roy M.; Smeaton, Laura M.; D'Aquila, Richard T.; Eron, Joseph J.; Currier, Judith S.; Gerber, John G.; Acosta, Edward; Sommadossi, Jean-Pierre; Tung, Roger; Snyder, Sally; Kuritzkes, Daniel R.; Murphy, Robert L. (The Journal of infectious diseases, 2001)
This prospective, multicenter, open-label study was designed to determine the antiretroviral activity and safety of a 4-drug regimen: 1000 mg indinavir every 8 h with 200 mg nevirapine, 40 mg stavudine, and 150 mg lamivudine, each given twice daily in amprenavir-experienced subjects. The primary end points of the study were the human immunodeficiency virus (HIV) RNA level and CD4 cell count responses. Fifty-six subjects were enrolled and were changed from amprenavir-containing regimens to the 4-drug regimen. Overall, at week 48, 33 (59%) of 56 subjects had HIV RNA levels <500 copies/mL (intent-to-treat analysis, where missing values equal ⩾500 copies/mL) and CD4 cell counts increased by 94 cells/mm3 from baseline. Subjects who had previously taken amprenavir combination therapy were more likely to experience virologic failure than those who had taken amprenavir monotherapy (odds ratio, 7.7; P=.0012). In this study, most subjects who had taken amprenavir-based regimens and who changed to a 4-drug regimen achieved subsequent durable virologic suppression